Role of Metformin and AKT Axis Modulation in the Reversion of Hypoxia Induced TMZ-Resistance in Glioma Cells - Lo Dico, Alessia; Valtorta, Silvia; Ottobrini, Luisa; Moresco, Rosa Maria (Frontiers in Oncology, 2019)
Hypoxia is a key driver of tumor adaptation promoting tumor progression and resistance to therapy. Hypoxia related pathways might represent attractive targets for the treatment of Glioblastoma Multiforme (GBM), that up to date is characterized by a poor prognosis. Primary aim of this study was to investigate the role of hypoxia and hypoxia-related modifications in the effect of temozolomide (TMZ) given alone or in association with the antidiabetic agent Metformin (MET) or the PI3K/mTOR blocker, BEZ235. The study was conducted in the TMZ responsive U251 and resistant T98 GBM cells. Our results showed that during hypoxia, TMZ plus MET reduced viability of U251 cells affecting also CD133 and CD90 expressing cells. This effect was associated with a reduction of HIF-1α activity, VEGF release and AKT activation. In T98 TMZ-resistant cells, TMZ plus MET exerted similar effects on HIF-1α. However, in this cell line, TMZ plus MET failed to reduce CD133 positive cells and AKT phosphorylation. Nevertheless, the administration of the dual PI3K/mTOR inhibitor BEZ235 potentiated the effect of TMZ plus MET on cell viability, inducing a pro-apoptotic phenotype during hypoxic condition also in T98 cells, suggesting the block of the PI3K/AKT/mTOR pathway as a complementary target to further overcome GBM resistance during hypoxia. In conclusion, we proposed TMZ plus MET as suitable treatment to revert TMZ-resistance also during hypoxia, an effect potentiated by the inhibition of PI3K/mTOR axis.